2016
DOI: 10.1002/cssc.201501625
|View full text |Cite
|
Sign up to set email alerts
|

Selective Conversion of 5‐Hydroxymethylfuraldehyde Using Cp*Ir Catalysts in Aqueous Formate Buffer Solution

Abstract: The highly selective hydrogenation/hydrolytic ring-opening reaction of 5-hydroxymethylfuraldehyde (5-HMF) was catalyzed by homogeneous Cp*Ir(III) half-sandwich complexes to produce 1-hydroxy-2,5-hexanedione (HHD). Adjustment of pH was found to regulate the distribution of products and reaction selectivity, and full conversion of 5-HMF to HHD with 99 % selectivity was achieved at pH 2.5. A mechanistic study revealed that the hydrolysis/ring-opening reaction of 2,5-bis-(hydroxymethyl)furan is the important inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 47 publications
(25 reference statements)
5
60
0
Order By: Relevance
“…However, these methods require high H 2 pressures and selectivities vary from 57 % to 81 %. Higher HHD selectivities are obtained in processes catalyzed by homogeneous catalysts . In particular, Cp*Ir III half‐sandwich complexes have appeared to be most promising …”
Section: Methodsmentioning
confidence: 99%
“…However, these methods require high H 2 pressures and selectivities vary from 57 % to 81 %. Higher HHD selectivities are obtained in processes catalyzed by homogeneous catalysts . In particular, Cp*Ir III half‐sandwich complexes have appeared to be most promising …”
Section: Methodsmentioning
confidence: 99%
“…Initially, we investigated the influence of electronic effect of substituents on TOF at different pH values. Two of the most active catalysts in our previous work, [Cp*Ir‐(di‐OMe‐bpy)(OH 2 )][SO 4 ] (di‐OMe‐bpy=4,4′‐dimethoxyl‐2,2′‐bipyridine) (catalyst 1) and [Cp*Ir‐(di‐OH‐bpy)(OH 2 )][SO 4 ] (di‐OH‐bpy=4,4′‐dihydroxyl‐2,2′‐bipyridine) (catalyst 2), were used to perform our experiments. Furfural, which is the typical product of dehydration of pentose, is hydrogenated under 1 MPa H 2 at 120 °C for one hour over 0.0083 mol % catalyst 1.…”
Section: Resultsmentioning
confidence: 43%
“…If we used hydroxyl as the substitute (catalyst 2), the highest TOF was 7340 h −1 at pH 5.0. We previously found that electron‐donating groups on the catalyst promoted the catalytic activity significantly . A small amount of GVL was observed if pH<1.5.…”
Section: Resultsmentioning
confidence: 43%
See 1 more Smart Citation
“…There were several reports on the conversion of HMF to HHD. Supported Pd, Pt and Au catalysts were proved to be effective for this conversion . Mentech and their group reported this conversion with 60% yield of HHD using Pt/C by the addition of oxalic acid for the first time .…”
Section: Introductionmentioning
confidence: 95%